Optimization of Distance Between Check-In Area and Boarding Gates: Case Study of Terminal 3 of Soekarno-Hatta Airport - Jamilah Fauziana Khoiriyyah; Heru Subiyantoro (Universitas Sebelas Maret Surakarta, 2024)
This research assesses the effect of the distance between Terminal 3’s check-in area and the boarding gate at Soekarno-Hatta Airport on passenger comfort. The focus is on how Terminal 3’s layout, which places a significant distance between these points, impacts passenger experience, satisfaction, and their preferred solutions. The study uses qualitative methods, observing Terminal 3 facilities and reviewing relevant literature. The expected outcomes include a deeper understanding of Terminal 3’s layout’s influence on passenger satisfaction and the identification of management and design factors that could mitigate this issue. The research considers passenger perspectives and preferences to provide recommendations for enhancing passenger accessibility and comfort in Terminal 3.